Profile of Schizophrenia Aggressiveness with the Risk of Suicide based on the Personality and Social Performance Score - Mochammad Choirul Waro; Alifiati Fitrikasari (Scientia Psychiatrica, 2021)
Introduction: The risk of schizophrenia for suicide is 10%, of which 10% -15% of people with schizophrenia die of suicide at 20 years of follow-up. Aggressiveness is a factor to be watched out. Other factors are hallucinations, suicide, early-onset, history of schizophrenia, surveillance, age, gender, education, genetics, and the effect of depression. This study aimed to describe the sociodemographic profile, aggressiveness, and hallucinations of suicide in schizophrenic patients. Methods: The design of this study is descriptive research. The number of samples in this study was 49 schizophrenic patients at risk of suicide. The risk of aggressiveness is measured by the Personality and Social Performance Score. Results. Of the 49 patients, it was found that the proportion of male patients was 31 people (63.3%) and 18 women (36.7%). Aggressive behavior based on PSP score was divided into modest aggressiveness of 22 people (44.9%), severe 20 people (40.8%), and very severe in two people (4.1%). Suicidal hallucinations were also found in 11 patients (22.4%). Conclusion: There are markedly aggressive behavior and hallucinations of suicide in the majority of schizophrenic patients.